Social network measures to match analysis in soccer : a survey - Manuel Clemente, Filipe (2016)
In this study we will present the most common and adequate network measures to analyse graph properties and to inspect the prominence of each player on a soccer team. Both approaches can provide a range of useful information. This kind of analysis will help to identify the prominence of players and also characterize the collective organization and patterns of the teams. General measures and centrality levels will be described and the applications will be discussed. By using social network analysis will be possible to quantify the structure of play and predict some behaviour. Such methodology will add new options to the field of match analysis.